Clinical use of Ortho-SUV transosseous hexapod in treatment of lower limb false joints - N. V. Tishkov; A. N. Rudakov; M. E. Puseva (Acta Biomedica Scientifica)
We studied the use of Ortho-SUV hexapod in the treatment of 15 patients with lower limb false joints. All patients were at active working age - from 22 to 50 years. 1n 12 patients, the period from the moment of trauma was 1 to 3 years, in 3 patients - 3 to 6 years. 5 patients had femoral false joints, 10 patients - shin false joints. 1n 98 % of cases, the formation of false joints was caused by inadequate treatment of initial trauma. 1n 100 % of cases, false joint localized at diaphyseal level and was accompanied with shortening of injured segment for 2.5 ± 1.0 cm in 13 patients, and for 0.5 and 0.8 cm in 2 cases. We also registered recurvatum and valgus deformity in 5 patients, recurvatum and varus deformity in 8 patients, and antecurvatum and varus deformity in 2 patients. Combined contracture in knee and ankle joint was found in 90 % of patients. Using combined transosseous osteosynthesis along with Ortho-SUV hexapod allowed us to correct hip deformity for 35 ± 10 days and ankle deformity - for 20 ± 5 days on the average. When shortening of femoral bone for more than 5.0 cm, the deformity was corrected in two stages. At the first stage, we reconstructed the length of a segment using methods of transosseous osteosynthesis at discrete-continuum distraction. At the second stage, we corrected deformity using Ortho-SUV hexapod within specified time limits. Duration of femoral and shin false joint consolidation was 194 ± 16 days. We registered inflammatory complications in the areas of transosseous elements contacting soft tissues in 3 (0.2 %) patients. These complications didn't have an effect on the treatment results.